Upaya Peningkatan Hasil Belajar Siswa Kelas X Fase 2 Dalam Pembelajaran Sosiologi Menggunakan Model The Power of Two di SMAN 3 Padang - Zariffullah Zariffullah; Buchari Nurdin; Sarbaitinil Sarbaitinil (CV. Rayyan Dwi Bharata, 2024)
This research is motivated by the low learning outcomes of class X Phase E2 students in learning Sociology at SMAN 3 Padang. The purpose of this study is to improve student learning outcomes by using The Power of Two model. This research method is Classroom Action Research (PTK) formulated by Ari Kunto which consists of four components, namely (1) Planning, (2) Action, (3) Observation/evaluation, (4) Reflection, with a mixed approach or Mixet Methods. The data of this research is in the form of information about the data on the results of actions obtained from the results of observations, the results of observation of teacher activities, the results of student affective assessments and student learning outcome tests. This research was carried out in 3 cycles. The results of the 1st cycle of research obtained an average student score of 76.83 with 15 (41%) students completing 21 (58%). In the second cycle, the average score of students was 78.86 with student completeness increasing to 22 (61.11%) and incomplete students 14 (38.88%). In the third cycle, the average score of students was 85.25 with student completeness increasing by 32 (88.88%) and incomplete students by 4 (11.11%). This means that in the third cycle the research target has been achieved. Based on the results of the research conducted, it can be concluded that the application of The Power of Two model in Sociology learning can improve students' cognitive learning outcomes, namely from 41% in cycle I increased to 61.11% in cycle II, increased again to 88.88% in cycle III.